"Makro" Program: A Way to Minimize Depressive Symptoms in Teenagers - Utari, Herlini; Retnowati, Sofia (ANIMA Indonesian Psychological Journal, 2011)
Depression is one among many other psychological problems found among teenagers. The objective of this research is to measure the effect of the “Makro” (Membangun Adaptasi dan Kompetensi Remaja Berisiko) – Building Reckless Youths’ Adaptation and Competencies Program in reducing depression symptoms. Subjects were high school students (N = 28), aged 15- 16 years, divided into 14 students as experiment group and the other 14 students as control group. Intervention in the form of MAKRO program consists of three components: reasoning management, stress management, and social skills. The measurement of the depression level during pre-test, post-test, and follow-up was conducted using the Beck Depression Inventory (BDI). Results were analyzed using Anova mixed models. It show a significant difference between control and experiment groups (p< .05). Based on the analysis of the results, MAKRO program is able to reduce the depression symptoms with 30.2% effective contribution after a 5- week follow-up measurement after treatment. Depresi merupakan gangguan psikologis yang banyak terjadi pada remaja. Penelitian ini bertujuan untuk mengetahui pengaruh program Membangun Adaptasi dan Kompetensi Remaja Berisiko (MAKRO) dalam menurunkan gejala depresi. Subjek adalah siswa SMA (N=28) berusia 15-16 tahun, yang terbagi dalam 14 siswa kelompok eksperimen dan 14 siswa kelompok kontrol. Intervensi berupa pelatihan MAKRO terdiri atas 3 komponen materi yaitu manajemen pikiran, manajemen stres dan keterampilan sosial. Pengukuran tingkat depresi pada pre-test, post-test dan follow-up dilakukan dengan Beck Depression Inventory (BDI). Hasil penelitian dianalisis dengan anova mixed models (anava campuran). Hasil penelitian menunjukkan bahwa ada perbedaan yang signifikan antara kelompok kontrol dan kelompok eksperien (p< .05). Berdasarkan hasil analisis tersebut program MAKRO dapat menurunkan gejala depresi dengan sumbangan efektif 30,2% pada pengukuran follow-up 5 minggu setelah perlakuan.